Social Reproduction and Depletion - Rai, Shirin M (feminists@law, 2023)
Social reproduction is not costless. When unrecognised, valorised but not valued, social reproduction leads to depletion of those who care. Building on the arguments of feminist international political economists, I examine the importance of taking the work of care seriously. Depletion through social reproduction occurs when resources for social reproduction fall below a threshold of sustainability over time. To know the intensity and extensity of depletion allows us to reveal not only the distress – physical, emotional/mental and social - but also to strategise towards reversing depletion.